The Existence of Mangaji Tudang Method in Enhancing Students’ Arabic Skills at Islamic Boarding Schools - Kartini, Kartini (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Islamic boarding schools play a significant role to run the best education to dig up knowledge for young generation. The integration of the national curriculum into Islamic boarding schools (pesantren) has become a serious concern in education system in Indonesia. Language teaching methods took a part to facilitate the language teaching and learning. This study discusses mangaji tudang method conducted in Ma’had Aly As'adiyah, Sengkang. This qualitative study discusses the method used by teachers in the Nahwu learning process. The data were collected through interview, observation, literature review and documentary. The data were analysed through coding process. The results of the study show that Mangaji Tudang carried out in Ma'had Aly As'adiyah Sengkang is a tradition of Islamic Boarding School learning models that integrates Islamic studies and Arabic language skills focusing on the integration of reading, listening, and writing skills. The most significant outcomes of the method are reading skills and mufradat (vocabulary) mastery.